2020
DOI: 10.32890/mmj.24.2020.8776
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Organizational Climate for Innovation and Innovative Work Behavior: Mediating Role of Employee Engagement in Pakistan

Abstract: The purpose of this study is to empirically investigate the mediating result of employee engagement between organisational climate for innovation and innovative work behaviour. This study will have positive contribution towards theory. The tool used for data collection was closed-ended questionnaire. Results indicated that organisational climate for innovation and innovative work behaviour has a direct and indirect impact on innovative work behaviours. In this study, employee engagement has partial mediation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
0
4
0
2
Order By: Relevance
“…Iklim organisasi telah menunjukkan pengaruh yang kuat terhadap employee engagement (Fanis & Rahmi, (2016) dalam Hadinata et al, (2019). Hasil penelitian yang telah dilakukan oleh Hadinata et al, (2019) dan Ali et al, (2020) menunjukkan bahwa iklim organisasi berpengaruh terhadap employee engagement. Berdasarkan asumsi di atas, maka diajukan hipotesis sebagai berikut: H4: Iklim organisasi berpengaruh terhadap Employee Engagement Hubungan Kepemimpinan Transformasional DenganEmployee Engagement…”
Section: Hubungan Iklim Organisasi Dengan Employee Engagementunclassified
See 1 more Smart Citation
“…Iklim organisasi telah menunjukkan pengaruh yang kuat terhadap employee engagement (Fanis & Rahmi, (2016) dalam Hadinata et al, (2019). Hasil penelitian yang telah dilakukan oleh Hadinata et al, (2019) dan Ali et al, (2020) menunjukkan bahwa iklim organisasi berpengaruh terhadap employee engagement. Berdasarkan asumsi di atas, maka diajukan hipotesis sebagai berikut: H4: Iklim organisasi berpengaruh terhadap Employee Engagement Hubungan Kepemimpinan Transformasional DenganEmployee Engagement…”
Section: Hubungan Iklim Organisasi Dengan Employee Engagementunclassified
“…Hasil penelitian menunjukkan bahwa iklim organisasi berpengaruh terhadap employee engagement. Hal ini juga sejalan dengan hasil penelitian yang dilakukan oleh Ali et al, (2020)yang menunjukkan bahwa iklim organisasi berpengaruh terhadap employee engagement artinya semakin baik iklim organisasi yang dirasakan oleh pegawai maka semakin tinggi employee engagement yang dimiliki oleh pegawai tersebut. Iklim organisasi yang positif akan memberikan rasa memiliki bagi pegawainya.…”
Section: Oleh Karena Itu Dapat Disimpulkan Bahwa Data Yang Digunakan ...unclassified
“…Moreover, employee engagement is a mediating construct of relevance to many studies. For example, employee engagement was found to have a mediating effect between leadership and occupational success (Vincent-Hoper et al, 2012); quality of work life and employee voice/neglect, exit intentions (Wahlberg et al, 2017), as well as organisational climate for innovation and innovative work behaviour (Ali et al, 2020). Therefore, the present study also sought to examine the mediating role of employee engagement between quality of work life and lifelong learning.…”
Section: Introductionmentioning
confidence: 92%
“…In a study by Ali et al (2020), it was found that employee engagement partially mediated the relationship of organisational climate for innovation and innovative work behaviour. This shows that the climate in the organisation plays a contributory role in the proliferation of employee engagement at the workplace.…”
Section: Employee Engagementmentioning
confidence: 99%
“…Numerous academics have conducted studies investigating the factors affecting IWB such as leadership style (Bin Saeed et al, 2019;Iqbal et al, 2022;Joo et al, 2023;Stanescu et al, 2020;Sudibjo & Prameswari, 2021), proactive personality (Yang et al, 2020), personal values (Purc & Lagun, 2019), perceived organizational support (Sulaiman et al, 2019), organizational climate (Ali et al, 2020), cultural intelligence , employee engagement (Ali et al, 2022), knowledge sharing (Nguyen et al, 2020), HRM practices (Bos-Nehles & Veenendaal, 2019) and external factor . Despite its significance, understanding the factors that drive this behavior remains fragmented and uneven (Stankevičiute et al, 2020).…”
Section: Introductionmentioning
confidence: 99%